Traditional production and main characteristics of Galichki kashkaval - Santa, Dushica; Srbinovska, Sonja (My University, 2014)
In this study, principles of traditional production and main characteristics of the traditional sheep cheese Galichki kashkaval from Bistra Mountain are presented. The contents of main components during ripening and storage of cheese were monitored. Analyses were performed on 1st, 30th, 60th and 100th day of ripening and 180th and 360th day of storage. On the first day cheese samples contained 20.75 % fat, 11.88 % total proteins, 1.20 % salt and 3.54 % ash. After 100 days of ripening cheese samples contained 27.87 % fat, 23.05 % total proteins, 2.02 % salt and 4.85 % ash. The technology process of kashkaval production was described in details. This cheese was produced and prepared in specific geographical area and fulfills the requirements listed in the National Law on quality of agricultural products. The data from this research might be a good starting point in the process of achieving the protected geographical indication.
Keywords: kashkaval cheese; sheep milk; traditional production